Perbedaan Pengaruh Model Student Teams Achievement Division (Stad) dan Numbered Heads Together (NHT) Terhadap Hasil Belajar Matematika Siswa Kelas V SD - Nur Halimah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
This study aimed to determine the significance of the influence differences between the use of Student Teams Achievement Division (STAD) model and Numbered Heads Together (NHT) model on the 5th grade mathematics learning outcomes in SD Negeri Sumberejo 01 and SD Negeri Sumberejo 02. The type of research used was a quasi experiment with an unpredictable Pretest Posttest design. The subjects of the study were students of grade 5 in SD N Sumberejo 01 as experimental class 1 and grade V SD N of Sumberejo 02 as experiment class 2. The variables in this study consisted of independent variables, namely Student Teams Achievement Division (STAD) model, Numbered Heads Together (NHT) model and dependent variable was learning outcome. Data collection was done by test technique. The data analysis technique used T test with Independent T test Sample applied to posttest value. Result of t test of posttest value of experiment group 1 and experiment group 2 showed that the value was in significance 0,019 ˂ 0,05, because the significance ˂ 0,05 hence Ho rejected and Ha accepted with conclusion there was significant difference between the model of STAD and NHT to the result of learning of mathematics at student grade 5 in SD Negeri Sumberejo 01 and SD Sumberejo 02. The significant difference in mathematics learning outcomes was supported by the difference average of two research samples, where the average of learning outcomes on the application of STAD learning model was 77.89, While the average of learning outcomes on the application of NHT learning model was 85.53. This meant that the learning treatment with NHT model has different significant impact compared to the STAD learning model on mathematics learning outcomes of grade 5 SD Sumberejo 01 and SD N Sumberejo 02 Semester II of 2016/2017academic year. Kata Kunci : Student Teams Achievement Division (STAD), Numbered Heads Together (NHT), Learning Outcomes, Mathematics, 5th grade primary school students